Recite doa for pilgrims in mobile application using Adobe Flash Lite / Nazihah Nasiman - Nasiman, Nazihah (2010)
Nowadays mobile technologies are drastically developed as the intermediary devices for several of fields such as learning, context aware, testing and etc. This research is focused on mobile as the intermediary devices, fields of mobile application, design of mobile interface, developing tools for mobile, human computer interface and the techniques uses. The research is focusing on applying Adobe Flash Lite as the development tools with additional features of Jawi font and audio of reciting the doa in the Adobe Flash Lite.